2004
DOI: 10.1101/gad.1241904
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb Ezh2 methyltransferase regulates muscle gene expression and skeletal muscle differentiation

Abstract: The Ezh2 protein endows the Polycomb PRC2 and PRC3 complexes with histone lysine methyltransferase (HKMT) activity that is associated with transcriptional repression. We report that Ezh2 expression was developmentally regulated in the myotome compartment of mouse somites and that its down-regulation coincided with activation of muscle gene expression and differentiation of satellite-cell-derived myoblasts. Increased Ezh2 expression inhibited muscle differentiation, and this property was conferred by its SET do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
570
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(609 citation statements)
references
References 72 publications
38
570
1
Order By: Relevance
“…The Snail, but not Yin-Yang (YY) 1, contributes to the recruitment of EZH2 and HDAC1/2 to the promoter of E-cadherin Recently, evidence has been reported that the mammalian protein YY1 may contribute to the process of PRC2 recruitment to the promoter region of different target genes (Satijn et al, 2001;Schwartz and Pirrotta, 2007;Simon and Kingston, 2009), and that YY1 is needed for H3k27 methylation of target genes in muscle cells (Caretti et al, 2004). Thus, we proposed that besides Snail, YY1 may also participate in the recruitment of EZH2, to the E-cadherin promoter.…”
Section: Hdac1/2-mediated Ezh2 and Snail Interaction In Npc Cellsmentioning
confidence: 99%
“…The Snail, but not Yin-Yang (YY) 1, contributes to the recruitment of EZH2 and HDAC1/2 to the promoter of E-cadherin Recently, evidence has been reported that the mammalian protein YY1 may contribute to the process of PRC2 recruitment to the promoter region of different target genes (Satijn et al, 2001;Schwartz and Pirrotta, 2007;Simon and Kingston, 2009), and that YY1 is needed for H3k27 methylation of target genes in muscle cells (Caretti et al, 2004). Thus, we proposed that besides Snail, YY1 may also participate in the recruitment of EZH2, to the E-cadherin promoter.…”
Section: Hdac1/2-mediated Ezh2 and Snail Interaction In Npc Cellsmentioning
confidence: 99%
“…(56) In undifferentiated mouse myoblasts, endogenous EZH2 is associated with YY1 and both it and YY1 were detected, along with the histone deacetylase HDAC1, at genomic regions of silent muscle-specific genes. (57) Their presence correlated with methylation of K27 of histone H3 and YY1 is required for EZH2 binding because RNA interference of YY1 abrogated chromatin recruitment of EZH2 and prevented H3-K27 methylation. (57) These results suggest that YY1 is involved in the silencing of tissue-specific genes in undifferentiated cells.…”
Section: Introductionmentioning
confidence: 99%
“…(57) Their presence correlated with methylation of K27 of histone H3 and YY1 is required for EZH2 binding because RNA interference of YY1 abrogated chromatin recruitment of EZH2 and prevented H3-K27 methylation. (57) These results suggest that YY1 is involved in the silencing of tissue-specific genes in undifferentiated cells. It remains to be established, however, whether this silencing can be mediated by Alu-associated BS for YY1.…”
Section: Introductionmentioning
confidence: 99%
“…One of epigenetic modifications, methylation of histone tail is thought to play an important role for cell fate determination (Zhang and Reinberg 2001;Jenuwein and Allis 2001;Kouzarides 2002). In recent studies, it is reported that Polycomb group (PcG) and trithorax group (TrxG) regulate differentiation state of embryonic cells by methylating histone H3 lysine 27 (H3K27), H3K4 and H3K9 of differentiation factor genes locus, such as homeobox (Hox), Distal-less homeobox (Dlx) paired box (Pax) and sine-oculis-related homeobox (Six) gene locus (Caretti et al 2004;Szutorisz et al 2005;Azuara et al 2006;Boyer et al 2006;O'Neill et al 2006;Rinn et al 2007;Reik 2007). The SET domain is a catalytic domain conserved among lysine methyltransferases proteins and more than 60 SET protein genes are identified in various organisms (Jenuwein et al 1998;Trievel et al 2002;Qian and Zhou 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The SET domain is a catalytic domain conserved among lysine methyltransferases proteins and more than 60 SET protein genes are identified in various organisms (Jenuwein et al 1998;Trievel et al 2002;Qian and Zhou 2006). For examples, Ezh2 which is a member of PcG regulates myogenesis by histone H3-K27 methylation (O'Carroll et al 2001;Czermin et al 2002;Caretti et al;. Mll and Mll2 involved in TrxG sustain Hox genes regulation in normal development (Yu et al 1995;Yu et al 1998;Hanson et al 1999;Glaser et al 2006).…”
Section: Introductionmentioning
confidence: 99%